Whole Transcriptome Analysis Identifies the Taxonomic Status of a New Chinese Native Cattle Breed and Reveals Genes Related to Body Size - Zheng, Xiao-Dong; Cheng, Jin; Qin, Wen-Juan; Balsai, Nyamsuren; Shang, Xuan-Jian; Zhang, Meng-Ting; Chen, Hong-Quan (Frontiers in Genetics, 2020)
Wandong (WD) cattle is identified as a new Chinese native cattle breed by the National Commission for Livestock and Poultry Genetic Resources recently, the population size of this breed is less than 10,000. WD cattle and Dabieshan (DB) cattle are sympatric but are raised in different ecological environments, on mountains and plains, respectively, and the body sizes of these two breeds are markedly different. Blood samples were obtained from 8 adult female WD cattle and 7 adult female DB cattle (24 months old). Total RNA was extracted from leukocyte cells, and sequencing experiments were conducted on the Illumina HiSeqTM 4000 platform. After the removal of one outlier sample from the WD cattle breed informed by principal component analysis (PCA), phylogenetic and population structure analyses indicated that WD and DB cattle formed a distinct Central China cattle group and showed evidence of hybridization between B.taurus and B.indicus. The immune-regulator CD48 (P=1.3E-6) was associated with breed-specific traits according to loss-of-function variant enrichment analysis. In addition, 113 differentially expressed genes were identified between the two breeds, many of which are associated with the regulation of body growth, which is the major difference between the two breeds. This study showed that WD cattle belong to the group of hybrids between B. Taurus and B. indicus, and identified one novel gene associated with breed traits and multiple differentially expressed genes between these two closely related breeds. The results provide insights into the genetic mechanisms that underlie economically important traits, such as body size, in cattle.